Priorities for ecological research on cetaceans in the Galápagos Islands - Palacios, Daniel M.; Cantor, Mauricio (Frontiers in Marine Science, 2023)
Located in the eastern tropical Pacific, the Galápagos Islands are an oceanic insular ecosystem subject to strong environmental variability driven by local and regional processes. Past research has shown that such conditions can attract and sustain at least 23 cetacean species, out of which 14 are common, including nine Delphinids, one Ziphiid, one Physeterid, and three Balaenopterids. These species occupy both coastal and oceanic habitats, most are present year-round, and a few are migratory. However, research on cetaceans in Galápagos has been sporadic and chronically underfunded and is not currently considered a priority in the research agenda for Galápagos. Based on a review of existing information and an assessment of knowledge gaps, here we identify priorities for ecological research on cetaceans in Galápagos along five topical areas: 1) spatiotemporal occurrence, 2) population assessment, 3) health assessment, 4) social ecology, and 5) trophic ecology. Addressing these knowledge gaps will also help inform actions to preserve cetacean biodiversity and to manage human activities involving or affecting cetaceans in Galápagos. Given the logistical and funding challenges of conducting cetacean research in Galápagos, we recommend optimizing data sampling and accessibility via integrated research protocols and open data repositories. We also recommend capitalizing on local citizen science activities, such as those conducted from cruise ships and whale-watching tours, which can serve as platforms of opportunity for obtaining basic data, thereby contributing to long-term data acquisition. Our proposed priorities should be assessed by Ecuadorian and Galápagos governmental institutions in broad and inclusive consultation with stakeholders and the scientific community prior to development and implementation of a research agenda. Collectively, these efforts will advance our understanding of the ecological role that marine megafauna, such as cetaceans, play in Galápagos and other oceanic islands, including maintaining large-scale connectivity and mitigating climate change.